Examining Mental Fatigue in Auditory Rehabilitation: Impact of Hearing Loss and Tinnitus - Satu Turunen-Taheri; Per-Inge Carlsson; Elisabeth Ternevall; Sten Hellström (Medical Research and Its Applications Vol. 2, 2024)
Background: Tinnitus, hearing loss and mental fatigue are multidimensional. Tinnitus may lead to a reduced health-related QoL affecting domains such as physical functioning, vitality and mental health. Aim: The purpose of this study was to identify and determine the degree of mental fatigue in patients with hearing loss and/or tinnitus participating in audiological rehabilitation, and to examine the self-reported Mental Fatigue Scale (MFS) in this patient group. Methods: Patients undergoing audiological rehabilitation at the Department of Audiology and Neurotology, Karolinska University Hospital, Sweden, 2011-2017, who completed a self-reported MFS questionnaire were investigated. Data on 76 consecutive patients were analysed in this pilot study. Patients were also assessed with the Tinnitus Handicap Inventory (THI). Data from medical records, MFS and THI were analysed with e.g. t-tests, chi-square tests, and correlation analysis. Some potential limitations are that the present study had no control group, and used retrospective data collected during clinical visits. Results: The study population had an age range of 38-65 years, and most had normal hearing (37%) or mild-to-moderate hearing loss (46%). Only 17% had severe-to-profound hearing loss. A total of 56.5% had tinnitus, of whom 39.5% scored \(\)57 on the THI, indicating severe tinnitus, whereas 43.5% reported no tinnitus. The MFS scores, ranged 13-42.5 points, were divided into three severity levels for analysis: 10.5-15 (mild), 15.5-20 (moderate) and \(\)20.5 (severe symptoms). In total, 67% of the patients had severe MFS scores \(\)20.5. Importantly, most of the participants (90%) with a THI score \(\)57 belonged to that group. There were 17 patients with normal hearing with MFS scores \(\)20.5. MFS scores \(\)30 and THI scores 78-100 were found in 11 patients. A significant positive correlation between MFS and severe tinnitus was found. Conclusions: The study reveals that severe mental fatigue is more common in patients with severe tinnitus than sole hearing loss.